Cost-effectiveness analysis of autogenous arteriovenous fistula, arteriovenous graft, and tunneled-cuffed catheter for hemodialysis in patients with end-stage kidney disease in Southern China - Wong, Tak-Sui; Chen, Qian; Zhong, Qiongqiong; Hu, Bo; Feng, Guanrui; Huang, Fengqiu; Lu, Jian; Yin, Lianghong; Yu, Zongchao; Akinwunmi, Babatunde O; Huang, Jian; Zhang, Casper Jp; et al. (The journal of vascular access, 2024)
To evaluate the cost-effectiveness of three permanent vascular accesses for maintenance hemodialysis patients from a hospital perspective throughout 5 years, which is the average life expectancy of patients with end-stage kidney disease. We conducted a EuroQol(EQ-5D) questionnaire survey between January 2021 and March 2021 with 250 patients to estimate the health utility of various states in patients under different hemodialysis vascular access. We designed a Markov model and conducted a cost-effectiveness analysis to compare the cost-effectiveness of three hemodialysis vascular access in Guangzhou throughout 5 years. The mean costs were US$44,481 with tunneled-cuffed catheter (TCC), and US$68,952 and US$59,247 with arteriovenous graft (AVG) and autogenous arteriovenous fistula (AVF), respectively. The mean quality-adjusted life-years (QALYs) was 1.41 with TCC, and 2.37 and 2.73 with AVG and AVF, respectively. AVG had an incremental cost-effectiveness ratio (ICER) of US$25,491 per QALY over TCC; AVF had an ICER of -US$26,958 per QALY over AVG. At a willingness to pay below US$10,633.8 per QALY, TCC is likely the most cost-effective vascular access. At any willingness to pay between US$10,633.8 and US$30,901.4 per QALY, AVF is likely the most cost-effective vascular access. These findings illustrate the value of AVF given its relative cost-effectiveness to other hemodialysis modalities. Although AVG costs much more than TCC for slightly higher QALYs than TCC, AVG still has a greater advantage over TCC for patients with longer life expectancy due to its lower probability of death.